PERLINDUNGAN HUKUM SEBAGAI UPAYA PENGEMBALIAN HAK KORBAN PENIPUAN UANG KRIPTO MELALUI RESTITUSI - Az Zahra Zain Auralia; Abraham Ferry Rosando (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Cryptocurrency is a digital currency system in which users use digital payments for business activities carried out that serve as a standard currency. Cryptocurrency is the name used for a system called Cryptography. Cryptocurrency in virtual money is one of the varieties of investments. Where cryptocurrency is believed to have a high value and its circulation is also still high. Because the popularity of bitcoin has increased interest, it provides an opportunity for people from irresponsible society. The person will look for victims by offering to become an experienced bitcoin trader. With the lure mode, it will reduce the risks in bitcoin trading and increase profits in a short time and the funds that can be withdrawn at any time will certainly succeed in attracting potential investors who are victims of it. Until now, cases of fraud with this mode have greatly increased in Indonesia. A side effect of crypto money fraud is loss of assets or assets of the victim as an investor, so here the author examines compensation through restitution with the aim of granting restitution to alleviate the suffering of victims, as a way to rehabilitate convicts, facilitate the judicial process and reduce threats or reactions. society in the form of acts of revenge by paying attention to the Restorative Justice approach